Assessment of Aesthetic Quality of Urban Landscapes by Integrating Objective and Subjective Factors: A Case Study for Riparian Landscapes - Zhang, Na; Zheng, Xiaorou; Wang, Xin (Frontiers in Ecology and Evolution, 2022)
To improve human well-being, there is increasing awareness of elevating aesthetic benefits by landscape design, planning, and management. However, which landscape features and attributes may be associated with aesthetic value of an urban landscape, human aesthetic preference, and landscape practices is still not clear yet. We proposed a comprehensive aesthetic assessment approach to realize the determination of landscape aesthetic indicators, integration of objective indicators and subjective preferences, and validation of estimations. The approach was based on a four-level landscape aesthetic indicator system from the bottom features up to attributes (landscape naturalness, landscape complexity, plant species diversity, water surface, water clarity, and bank naturalness), component qualities, and finally overall quality. Fourteen metrics that could provide objective visual and spatial characters and ecological implications were identified and quantified to indicate landscape aesthetic features. Landscape aesthetic attributes, vegetation and waterbody component qualities, and overall quality were estimated by integrating objective indicators and human subjective preferences. The approach was applied to a case study of four subareas along an artificially restored riparian buffer in Beijing, China. The results showed that the modeled overall aesthetic quality was determined by both vegetation (accounting for 53%) and waterbody. The higher vegetation quality depended on the higher plant abundance, more vegetation patches, and more vegetation patch types; the higher waterbody quality depended on the clearer water and larger water surface. Compared with other features, vertical vegetation configuration, diversity of patch type and patch shape, and shrub species diversity had greater contribution to the attributes of naturalness, complexity, and plant species diversity, respectively. The modeled vegetation aesthetic attributes were directly validated using the surveyed perceptions, and the modeled vegetation and waterbody aesthetic qualities were indirectly validated by correlating with the main recreational activities. The approach is confirmed to be able to address the questions on determination, integration, and validation of landscape aesthetic indicators in some way. Thus, the approach is expected to be used for other landscapes to offer a framework for landscape practices to improve aesthetic value and cultural service.